Prototype isochoric preservation device for large organs - Șerban, Alexandru; Năstase, Gabriel; Beșchea, George-Andrei; Câmpean, Ștefan-Ioan; Fetecău, Cătălin; Popescu, Irinel; Botea, Florin; Neacșu, Ion (Frontiers in Bioengineering and Biotechnology, 2024)
This paper presents the design and prototype of a constant volume (isochoric) vessel that can be used for the preservation of large organs in a supercooled state. This prototype is a preliminary version of a more advanced design. The device consists of a cooling bath operated by a mechanical vapor compression refrigeration unit and an isochoric chamber made of stainless steel. The preservation of organs using supercooling technology in an isochoric chamber requires a continuous temperature and pressure monitoring. While the device was initially designed for pig liver experiments, its innovative design and preservation capabilities suggest potential applications for preserving other organs as well. The isochoric reactor may be used to accommodate a variety of organ types, opening the door for further research into its multi-organ preservation capabilities. All the design details are presented in this study with the purpose of encouraging researchers in the field to build their own devices, and by this to improve the design. We chose to design the device for isochoric supercooling as the method of preservation to avoid the ice formation.